Relationship between some level of physical measurements and the performance of some offensive skills in judo wrestling for Iraqi cadet national team players for ages (15 – 16) years. - Tariq Hassan, oday; Abdullah Hamad, Asaad (Journal of Physical Education, 2012)
The research included five parts, in 1st part, the researchers mentioned of the importance of research, presentation of the problem, and installs the objectives mentioned areas of research. 2nd part has included theoretical studies which were in regard to the subject. 3rd part, the researchers dealt with the research methodology and procedures, the research method was a survey - the study of relationships connectivity, then they across the research sample with details and the method chosen, then they mention to equipments and the tools which used to research and measurements of physical and skills of wrestling judo under consideration and referred also to the conduct of the tests skills, at the end of this part the researchers mention the means of statistical which used in the search. Part 4th the researchers offered from the results obtained through them and they analyzed and discussed these results. In Part 5th the researchers showing conclusions obtained from the analysis and discussion of results and finally the researchers mention some of the recommendations that came on regarding what the researchers concluded.